Carving on the parapet wall - sequences from the epic Ramayana - Seeta in Ashokavana; Below the parapet - carved miniatures of temple towers - Brig. Ajai Singh (2021)
[ Image courtesy: Brig A.P. Singh - www.collectingmoments.in ] Parapet wall carving - Ramayana sequences - Left to right 1 ) Mandodari requesting Ravana to return Seeta 2 ) Seeta sitting under a tree in Ashokavana with the demoness Trijata guarding her 3) Ravana's assistants faking Rama and Lakshmana's death to Seeta - two heads on the ground